Detecting novel genes for low-density lipoprotein cholesterol in European population using bioinformatics analysis. (May 2016) - Zhang, Huan; Mo, Xing-Bo; Xu, Tan; Lei, Shu-Feng; Zhang, Yong-Hong
Aim: The aim of this study was to identify related genes for low-density lipoprotein cholesterol and evaluate the functional relevance to provide evidences for prioritizing these genes.Materials & methods: We performed a gene-based association study in about 188, 578 individuals. Furthermore, we performed bioinformatics analyses to support the identified genes.Results: A total of 292 genes were found to be significant after Bonferroni correction (p < 2.3 × 10 -6 ). Among these genes, 59 seemed to be associated with coronary artery disease (CAD).Conclusion: The evidence obtained from the analyses of this study signified the importance of many genes, for example, LDLR, ABCG5, ABCG8, APOB, HNF1A, PTPN11, APOA5 and MCM6, which were also associated with CAD. The findings might provide more insights into the genetic basis of lipid metabolism and CAD.